Studies on Activator Formation in Human Plasma with Streptokinase - Martin, M; with the technical assistance of Frau R. Albrecht (Thrombosis and Haemostasis, 1973)
The activator concentrations developing during a streptokinase infusion treatment were measured on a quantitative basis. The reference value (100 per cent activator) selected for this purpose was the activator effectiveness resulting from a mixture of 20,000 units of streptokinase and 1 millilitre of citrate plasma. The streptokinase treatment regimens used for our study consisted either of a continuous streptokinase infusion treatment extended over three days or of intermittent streptokinase infusions with a 16-hour streptokinase-free interval. The highest activator concentrations measured had developed between 1 and 24 hours after the streptokinase treatment had started, the values being in the order of 0.4 per cent. When treatment was continued, the activator concentrations dropped below that level. Under the intermittent streptokinase regimen, the activator concentrations measured during the second series of infusions were always lower than those measured during the first series. The activator concentration levels and the plasminogen values measured simultaneously acted in a reciprocal manner, i.e. a plasminogen decrease corresponded to an activator increase and vice versa. Seen under the aspect of the obtainable maximum of activator effectiveness, the intermittent streptokinase infusion regimen offers no advantage as against the continuous treatment form. It would certainly be desirable to achieve higher activator levels through modifications in the streptokinase dosage.